2019
DOI: 10.1115/1.4041773
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Considerations for Nonlinear Dynamics of a Class of MEMS Switches Undergoing Tip Contact Bouncing

Abstract: Batch fabrication processes used to produce micro-electro-mechanical systems (MEMS) are prone to uncertainties in the system geometrical and contact parameters as well as material properties. However, since the common design method for these systems is typically based on precise deterministic assumptions, it is necessary to get more insight into their variations. To this end, understanding the influences of uncertainties accompanied by these processes on the system performance and reliability is warranted. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The dynamic pull-in voltage is determined for such switches and verified with that presented in a previous work [20]. It is worth noting that in the modeling of MEM switches, a realistic asperity-based contact model that has been used previously in many studies (see, e.g., [37]) is adopted here for the NEM switch model with the consideration of surface effects to represent the contact force along with the repulsive van der Waals force. However, it was demonstrated that the elastic forces due to asperities had negligible or no influence on the bouncing behavior.…”
Section: Resultssupporting
confidence: 53%
“…The dynamic pull-in voltage is determined for such switches and verified with that presented in a previous work [20]. It is worth noting that in the modeling of MEM switches, a realistic asperity-based contact model that has been used previously in many studies (see, e.g., [37]) is adopted here for the NEM switch model with the consideration of surface effects to represent the contact force along with the repulsive van der Waals force. However, it was demonstrated that the elastic forces due to asperities had negligible or no influence on the bouncing behavior.…”
Section: Resultssupporting
confidence: 53%